Peningkatan Keterampilan Orang Tua dalam Perawatan Luka Anak Pasca Operasi melalui Pendekatan Home Care - Fitri Afdhal; Indri Yani Oktasari; Sefti Loren; Selvi Selvi; Septiana Septiana; Sismayanti Sismayanti; Suci Yuliawaty; Miki Marisa; Widya Putri; Vira Sintha Patari; Nabilla Tri Agustiani; Utari Ramadani; Welly Yansyah; Sindi Yuliarti; Pebi Oktapiani; Made Dwi Wiratama; Taufik Indrajaya (JURNAL PENGABDIAN KADER BANGSA, 2026)
Postoperative wound care in children is a crucial aspect of the healing process and infection prevention. Lack of parental knowledge and skillsin wound care can increase the risk of surgical site infection (SSI) and delay recovery. Therefore, this community service program aims toimprove parental skills in caring for postoperative wounds in children through a home care approach. The method used in this program includes counseling, training, and mentoring conducted in Betung Induk, Abab District, Pali Regency. Evaluation was carried out by comparing participants' pre-test and post-test results and observing practical skills. The evaluation results showed an increase in participants' understanding from 42.8% in the pre-test to 85.7% in the post-test, as well as an improvement in wound care skills up to 78.6%. Although there were limitations in training time and the number of medical assistants, this program successfully enhanced parents' skills in postoperative wound care. In the future, this program can be developed through digital-based education and online mentoring to expand its reach and increase the effectiveness of health education.